The Influence of Prostate Volume on Magnetic Resonance Imaging Diagnostic Performance and the Adjunctive Role of Prostate‐Specific Membrane Antigen Positron Emission Tomography in Detecting Clinically Significant Prostate Cancer - Matthieu Bryan Chun‐Hei Mo; Sachin Joshi; William Harrison; Madeleine Bain; Nikhil Sapre; Devang Desai (Trends in Urology & Men's Health, 2026)
ABSTRACT To evaluate the influence of prostate volume on the diagnostic accuracy of multiparametric MRI (mpMRI) in detecting clinically significant prostate cancer (ISUP Grade ≥ 2), using radical prostatectomy (RP) histopathology as the reference standard. A secondary objective was to assess the adjunctive value of PSMA PET in identifying clinically significant cancer in cases where mpMRI findings were negative or low suspicion, particularly in larger prostate volumes. We conducted a multicentred regional observational study totalling 167 patients who underwent mpMRI, PSMA PET, transperineal (TP) biopsy and RP between October 2022 and February 2025. The average age across the total population was 65.6 years. The median PIRADS score across all patients was 4, and the average prostate specific antigen level at the time of imaging was 7.4 ng/mL. TP prostate biopsy methods included MRI‐ultrasound Fusion Monalisa ( n = 111) and traditional cognitive fusion biopsy methods, including grid and precision point ( n = 56). Prostate volumes were stratified into three categories: ≤ 20, 21–29 and ≥ 30 cc. The average age in each volume group was 63.2 years for ≤ 20 cc, 65.7 years for 21–29 cc and 67.9 years for ≥ 30 cc. The mean prostate volume within each group was 17.4, 25.1 and 48.6 cc, respectively. MpMRI‐reported ISUP grade groups were compared against final RP histopathology with reports performed by specialist uropathologists. Discrepancies were classified as underestimation or overestimation of histopathology. Statistical comparisons were performed using chi‐squared tests with significance set at p < 0.05. For the secondary objective, patients with negative or low suspicion on mpMRI (PIRADS ≤ 2) but were found to have ISUP ≥ 2 disease on RP were identified. In these discordant cases, PSMA PET imaging was reviewed to determine whether it correctly localised the index lesion, thereby assessing its adjunctive diagnostic value, particularly in larger prostates. Multiparametric MRI grading accuracy decreased significantly with increasing prostate volume: 78% concordance in the ≤ 20 cc group, 65% in the 21–29 cc group and 52% in the ≥ 30 cc group ( p = 0.012). Underestimation of tumour grade was the predominant discrepancy, particularly in prostates ≥ 30 cc, where clinically significant disease (ISUP ≥ 2) was frequently misclassified as ISUP 1. PSMA PET identified significant lesions in several mpMRI‐negative or low‐suspicion cases, particularly in larger prostate volumes. Multiparametric MRI accuracy in detecting clinically significant prostate cancer diminishes as prostate volume increases, likely due to decreased lesion conspicuity within enlarged transition zones. This limitation supports incorporating prostate volume into risk stratification and imaging interpretation, with consideration for adjunctive diagnostics such as PSMA PET or confirmatory biopsy in larger prostate volumes.